The Role of Arabic in the Global World - Ratna Komalasari (An Nazhair: Journal of Arabic Education, 2024)
Arabic is a language that is familiar to hear. Because now Arabic is also the second international language after English. In fact, Arabic is more popular than English, because Arabic is quite developed, especially in the middle east where the daily means of communication is Arabic. However, over time, English began to enter the Arabic environment, so that Arabic began to be displaced by English, especially English began to enter the field of education such as biology, physics and so on. Arabic also does not want to lose, because as long as Islam still exists Arabic will still exist. The method used is library qualitative research methodology. Because the author gets some data through some documentation obtained from several books, journals and so on. The purpose of knowing the role of Arabic in the global world is so that readers know the extent of the development of Arabic, especially during the development of this globalization. Because today it is not only Arabic that is the goal, but also other foreign languages such as mandarin, Korean, Japanese and so on. The result of this research is that Arabic will continue to increase and develop as long as islam still exists. Because Islam and Arabic came together. So, even though in this gen Z era Arabic began to be displaced by English, Arabic still holds many roles in people’s lives, including in utilizing technology. Many people use technological tools according to the devolvement of globalization both to facilitate in completing work, communicating distances, and as a medium of learning.